Degree of Biomimicry of Artificial Spider Silk Spinning Assessed by NMR Spectroscopy. (30th August 2017) - Otikovs, Martins; Andersson, Marlene; Jia, Qiupin; Nordling, Kerstin; Meng, Qing; Andreas, Loren B.; Pintacuda, Guido; Johansson, Jan; Rising, Anna; Jaudzems, Kristaps
Abstract: Biomimetic spinning of artificial spider silk requires that the terminal domains of designed minispidroins undergo specific structural changes in concert with the β‐sheet conversion of the repetitive region. Herein, we combine solution and solid‐state NMR methods to probe domain‐specific structural changes in the NT2RepCT minispidroin, which allows us to assess the degree of biomimicry of artificial silk spinning. In addition, we show that the structural effects of post‐spinning procedures can be examined. By studying the impact of NT2RepCT fiber drying, we observed a reversible beta‐to‐alpha conversion. We think that this approach will be useful for guiding the optimization of artificial spider silk fibers. Abstract : Strukturänderungen in den Enddomänen eines maßgeschneiderten Spinnenseide‐Protein (NT2RepCT) und eine β‐Faltblatt‐Umwandlung in der zentralen Wiederholungsregion wurden mit Lösungs‐ und Festkörper‐NMR‐Spektroskopie beobachtet. Aus den Ergebnissen lässt sich bewerten, inwieweit ein biomimetischer Faserspinnprozess stattfindet.